Synthesis and Spectroscopic Characterization of Some Copper(II) Trinuclear Complexes involving Nitrogen as Bridging Atoms - Annapoorani, S. (Asian Journal of Chemistry, 2012)
The following Schiff bases were employed as ligands in synthesizing Cu(II) trinuclear complexes: 1,2-bis-(2-aminobenzylideneamino) ethane (L1), 1,2-bis-(2- aminobenzylideneamino)propane (L2), 1,3-bis-(2-aminobenzylideneamino)propane (L3), 1,2-bis-(2-aminobenzylideneamino)benzene (L4). The ligands were obtained by reacting 2-aminobenzaldehyde with 1,2-diaminoethane, 1,2-diaminopropane, 1,3-diaminopropane and 1,2-diaminobenzene, respectively. Four trinuclear coordination complexes were synthesized and structurally characterized by elemental analysis, molar conductivity, FT-IR, UV-Visible, magnetic and EPR spectral studies. The results suggest that the complexes are trinuclear and ionic in nature.